Peran Badan Permusyawaratan Desa (BPD) Dalam Pengawasan Pengelolaanleuangan Desa (Di Desa Waiheru Kecamatan Teluk Ambon Baguala) - Erlita Erlita; Normawati Normawati; Pieters Pieters (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to analyze the role of the Village Consultative Body in supervising village financial management in Waiheru village, Teluk Ambon Baguala sub-district. The village consultative body has a strategic role in overseeing village funds so that they are not misused. This type of research is qualitative research aimed at knowing BPD supervision based on the problems discussed, namely problems that occur at the research location. The informants in this study were 7 people. Data collection by interview, observation, and documentation. Data analysis through data reduction, data presentation and conclusions, while data validity uses triangulation of sources, techniques and time.The results showed that the role of the Village Consultative Body in supervising village finances in Waiheru Village, Teluk Ambon Baguala Subdistrict was not optimal because of the lack of transparency of the village fund budget to the community and seen from the supervision indicators, namely measuring supervision whether in accordance with the initial plan, comparing supervision from the previous plan, and correcting performance if there is an error.